Pre-Service Teachers' Attitude on ELT Research - Martin Kustati; Hidayat Al-Azmi (Research in Social Sciences and Technology- OpenED Network, 2018)
This paper reports on a research determining the attitudes of pre-service EFL teachers' attitude to research in English language teaching (ELT) in Indonesia. A mixed method was used in this study. A survey questionnaire was completed by 217 (F= 187, M=30) participants who enrolled in the fourth year of undergraduate teacher education. Then, interview was used to identify their problems in conducting the research. The participants acknowledged that they had positive attitudes towards research in ELT. Meanwhile, they had negative views about English department involvement in their research. While there were no significant sex differences in the attitudes to ELT research. The interview findings revealed that there were some factors that made them get difficulties in doing their research. The pedagogical implications of the study for the pre-service teachers include the need to be aware of the significant relationship between attitude and background in research practice and they should be trained formally on conducting and writing ELT research.